Comparative Analysis of Sucrose and Moringa (Moringa oleifera Lam.) Leaf Extracts as Natural Additives to Prolong the Vase Life of Rose (Rosa x hybrida) Cut Flowers - Telebrico, Marjune (Journal of Interdisciplinary Perspectives, 2024)
Roses, one of the most iconic flowers in the world, symbolize love, beauty, and elegance. Their vibrant colors and soft petals make them popular for special occasions like weddings, anniversaries, and romantic gestures. People from different walks of life usually admire roses for their aesthetic appeal and pleasant fragrance. Both florists and consumers in the flower industry depend on keeping cut roses fresh. Placing roses in water-filled vases is a standard method to extend their lifespan. This study explored the effectiveness of natural additives in prolonging the life of cut roses. A completely randomized design (CRD) was used, and four treatments were used: distilled water (control), a sucrose solution, moringa leaf extracts, and a combination of sucrose and moringa. The roses were observed over eight days to assess various factors such as leaf drop, stem rotting, bent necks, petal drop, flower condition, and petal color. The results showed that the combined treatment of sucrose and moringa led to the highest number of leaf drops, with 15 leaves dropping by day five. Distilled water resulted in 12 dropped leaves, moringa extract caused four leaves to drop, and sucrose had the least impact, with only two leaves dropping. The combination treatment also caused the most significant stem rotting (32.75 mm) and the most bent necks (14 roses). In contrast, roses treated with sucrose or moringa separately had better outcomes, with the least bent necks and minimal leaf drops. The combined treatment again had the worst results for petal drops, with eight petals dropping, followed by distilled water with six petals. The overall flower condition was poorest with the combined treatment, scoring 1 (completely open/damaged), while roses treated with sucrose or moringa separately had better scores, indicating they remained fresher. Petal color was also most affected by the combined treatment, which resulted in a light brown color, whereas the separate treatments maintained a darker red hue. Hence, while sucrose and moringa are beneficial when used individually, their combination negatively impacts the longevity and appearance of cut roses.